Corralling, planting density, and N fertilizer rate effect on soil properties, weed diversity, and maize yield - Abdul Rahman, Nurudeen; Larbi, Asamoah; Opoku, A.; Tetteh, F.M.; Hoeschle-Zeledon, I. (Informa UK Limited, 2019)
The interaction effect of stocking density of sheep and goat corralling (SDSG), maize planting density (MPD), and N fertilizer rate (NFR) on soil properties, weed diversity, and maize yield were evaluated on-farm in a smallholder maize-livestock farming system of Northern Ghana during the 2014 and 2015 cropping seasons. A split-split plot design replicated on eight farms was used to study the effect of three SDSG (0, 70, and 140 head ha−1), three MPD (66 667, 100 000, and 133 333 plants ha−1), and three NFR (0–40-40, 60–40-40, and 90–40-40 NPK kg ha−1). The SDSG at 70 and 140 head ha−1 increased (P < 0.01) soil chemical and biological properties and weed diversity compared with the control in both cropping seasons. Maize growth, yield and yield components, and weed biomass were affected (P < 0.05) by the SDSG, MPD, and NFR interactions. Maize-livestock farmers with smaller flock size could use SDSG at 70 head ha−1 with NFR at 90 kg ha−1, whilst those with large flock size could stock at 140 head ha−1 with NFR at 60 kg ha−1 and MPD at 133 333 plants ha−1 for increased maize yield and weed management.